Left Subclavian Artery Aneurysm in a Child with Turner Syndrome: A Case Report - Brilla, Maria Alejandra Rodriguez; Trapp, Johnathon; Malhotra, Monesha Gupta; Bautista-Hernandez, Victor (Archives of Clinical and Medical Case Reports, 2024)
Turner syndrome is associated with congenital cardiac defects and vasculopathies in children, however association with a left subclavian artery aneurysm is extremely rare. We report a case of an 11-year-old girl with Turner syndrome and a left subclavian artery aneurysm. Aneurysmal repair was performed by exclusion and placement of a vascular Dacron graft from the distal left subclavian artery to the descending thoracic aorta. During the 10-month follow-up after surgery there is no evidence of aneurysmal recurrence, and the graft remains patent with no complications.